2013
DOI: 10.1097/bcr.0b013e3182a2a771
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Resuscitation in Morbidly Obese Burn Patients May Contribute to High Mortality

Abstract: Objective The rising number of obese patients poses new challenges for burn care. These may include adjustments in calculations of burn size, resuscitation, ventilator wean, nutritional goals as well as challenges in mobilization. We have focused this observational study on resuscitation in the obese patient population in the first 48 hours after burn injury. Prior trauma studies suggest a prolonged time to reach end points of resuscitation in the obese compared to non-obese injured patients. We hypothesize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…79 Similar findings were also reported in morbidly obese patients with severe burns. 73 Other investigations concentrated on examining the specific impact of abdominal obesity on organ failure. 61,80 The study of Paolini et al 61 showed that visceral adiposity was associated with intra-abdominal hypertension and higher occurrence of kidney failure.…”
Section: Obesity and Icu-associated Organ Failurementioning
confidence: 99%
“…79 Similar findings were also reported in morbidly obese patients with severe burns. 73 Other investigations concentrated on examining the specific impact of abdominal obesity on organ failure. 61,80 The study of Paolini et al 61 showed that visceral adiposity was associated with intra-abdominal hypertension and higher occurrence of kidney failure.…”
Section: Obesity and Icu-associated Organ Failurementioning
confidence: 99%
“…Existing studies have shown the errors in the LBC and RN approaches. As a larger percentage of the population qualifies as obese, these tools become more unreliable (Rae et al, 2013;Neaman et al, 2011;Berry et al, 2001;Livingston and Lee, 2001). An underestimation of the TBSA is likely with obese patients and higher body mass index (BMI).…”
Section: Related Workmentioning
confidence: 99%
“…6 296 adult patients with mean TBSA of 41% were taken up for study stated that being morbidly obese was an independent risk factor for death. Obese patients suffered persistent metabolic acidosis during resuscitation with high risk of multiple organ failure.…”
Section: Discussionmentioning
confidence: 99%